ANALISIS LAYANAN E-COMMERCE DALAM MENINGKATKAN PENJUALAN (STUDI KASUS PADA TOKO ERNI LABAY SHOPEE JAKARTA UTARA) - Nunik Intanisasi; Abbas Mansyur (JAMBIS : Jurnal Administrasi Bisnis, 2022)
The purpose of this study is to analyze E-commerce Services at Erni Labay Stores. This study uses qualitative data types. Data collection techniques using Interview, Documentation, and Observation. Data analysis uses primary and secondary data. At first the Erni Labay shop only sold offline, seeing technological developments finally the shop owner chose to sell online on the shopee platform. From the results of the research, the E-commerce services implemented at the Erni Labay Shopee Shop have been well and optimally systemized, starting from the order process, payment, delivery, information services or customer service. E-commerce services that make it easy for buyers to make purchase transactions, because the process is easy, fast and secure transactions are expected to be able to increase sales at the store. It's just that there are obstacles or problems that occur, product diversity, product innovation and lack of promotion,so that it can hinder the rate of increasing sales.